2009
DOI: 10.1111/j.1750-3639.2009.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Morpho‐Physiologic Characteristics of Dorsal Subicular Network in Mice after Pilocarpine‐Induced Status Epilepticus

Abstract: The goal of this study was to examine morpho-physiological changes in the dorsal subiculum network in the mouse model of temporal lobe epilepsy using extracellular recording, juxtacellular and immunofluorescence double labeling, and anterograde tracing methods. A significant loss of total dorsal subicular neurons, particularly calbindin, parvalbumin (PV), and immunopositive interneurons, was found at 2 months after pilocarpine-induced status epilepticus (SE). However, the sprouting of axons from lateral entorh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Therefore, a panoramic analysis beyond the temporal lobe of these epileptic mice is essential for better understanding the lesions and compensatory reorganization of circuitry in epilepsy. Currently, reorganizations of the neural circuits in several brain regions of this mouse epilepsy model including the hippocampus (Ma et al, 2006 ; Zhang et al, 2009 ), the subiculum (Tang et al, 2006 ; He et al, 2010 ) and the lateral entorhinal cortex (Ma et al, 2008 ) have been reported. Following these studies and our observations here on the amygdala, it will be of interest to analyze the reorganizations of other neural circuits directly connected with the hippocampus in epileptic mice, such as the v-Sub-retrosplenial cortex (RSC) circuits, perirhinal cortex (PRh)-hippocampus and PRh-entorhinal cortex (EC)-hippocampus circuits as well as prefrontal cortex-reuniens thalamic nucleus-hippocampus circuits.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, a panoramic analysis beyond the temporal lobe of these epileptic mice is essential for better understanding the lesions and compensatory reorganization of circuitry in epilepsy. Currently, reorganizations of the neural circuits in several brain regions of this mouse epilepsy model including the hippocampus (Ma et al, 2006 ; Zhang et al, 2009 ), the subiculum (Tang et al, 2006 ; He et al, 2010 ) and the lateral entorhinal cortex (Ma et al, 2008 ) have been reported. Following these studies and our observations here on the amygdala, it will be of interest to analyze the reorganizations of other neural circuits directly connected with the hippocampus in epileptic mice, such as the v-Sub-retrosplenial cortex (RSC) circuits, perirhinal cortex (PRh)-hippocampus and PRh-entorhinal cortex (EC)-hippocampus circuits as well as prefrontal cortex-reuniens thalamic nucleus-hippocampus circuits.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of observed seizure activity in young mice would support the hypothesis that mutation of Elfn1 may set into motion long-term epileptogenic processes that eventually lead to a seizure-prone brain [67] . Finally, Elfn1 is also expressed in subsets of interneurons in the hilus as well as in the neocortex and piriform cortex, and strongly in the dorsal subiculum, regions also known to exhibit epileptogenic activity [68] , [69] , [70] .…”
Section: Discussionmentioning
confidence: 99%
“…The subiculum is reported to be only partially damaged [ 50 , 62 ]. In the pilocarpine model of TLE, indeed, about 14% of ventral subicular neurons are lost in the molecular layer, while no loss is observed in the pyramidal cell layer [ 72 , 73 ].…”
Section: Neuronal Loss and Plasticitymentioning
confidence: 99%
“…In pilocarpine-treated rats a substantial reduction of parvalbumin-positive interneurons is evident in the subicular pyramidal cell layer, while a smaller loss is detected in the subicular molecular layer [ 63 , 72 ]. Loss of parvalbumin-positive cells is also described in CA1, dentate hilus, deep layers of entorhinal, perirhinal and insular cortices in pilocarpine-treated rats [ 63 , 73 , 87 , 88 , 96 - 98 ].…”
Section: Neuronal Loss and Plasticitymentioning
confidence: 99%